Catalyst slurry, preparation method and application thereof, membrane electrode and fuel cell
Catalyst slurry is prepared through tip ultrasonic, high-speed shear and high-pressure homogeneous shearing processes, and a catalyst layer with hierarchical functional distribution is formed through spraying processes, solving the waste of precious metals and ionomers caused by uneven distribution of the catalytic layer in the prior art, and achieving efficient catalyst utilization and improved membrane electrode performance.
Patent Information
- Application Number
- CN202211005348.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-08-19
AI Technical Summary
In the existing fuel cell membrane electrodes, the uniform distribution of the catalytic layer and the gradient distribution reactant system lead to excessive use and waste of precious metals and ionomers, making it difficult to achieve a catalytic layer with a hierarchical functional distribution.
The catalyst slurry is prepared by tip ultrasonic, high-speed shear and high-pressure homogeneous shearing processes, and a layered functional distribution of the anode catalyst layer is formed through the spraying process, and the structure and performance of the catalyst layer are optimized using different support and functional additives.
The uniform dispersion and effective utilization of the catalyst are achieved, the electrochemical performance and anti-aging ability of the membrane electrode are improved, the use of precious metals and ionomers is reduced, and waste is avoided.
Smart Images

Figure CN115188972B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a catalyst slurry, a preparation method and application thereof, and a membrane electrode and a fuel cell. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC, full name Proton Exchange Membrane Fuel Cell) has the advantages of compact structure, fast response speed, and environmental friendliness. As a clean power battery, it has broad application prospects and important practical significance in transportation fields such as heavy trucks, forklifts, and public transportation. The membrane electrode assembly (MEA, full name Membrane Electrode Assembly) is the core component of PEMFC, which is made by film formation and bonding of key raw materials such as proton membrane, catalyst layer, and gas diffusion layer.
[0003] The performance of the catalytic layer in MEA is not only related to the intrinsic reaction activity of the catalyst, but also to the composition of the catalytic layer slurry, the film-forming process of the catalytic layer, the microporous layer structure and distribution of the catalytic layer. The intrinsic reaction activity of the catalyst is mainly determined by the characteristics of the catalyst carbon carrier, the morphology, crystal form and distribution state of the precious metal. The catalytic layer slurry is generally composed of a catalyst, an ionomer dispersion, a solvent system and a functional additive. The film-forming processes of the catalytic layer mainly include spraying, direct coating and thermal transfer. Most membrane electrode production uses uniform cathode and anode catalytic layers, but in the actual electrochemical reaction process, various reactants and product systems are gradiently distributed in the layers and interlayer structures of MEA. The combination of a uniformly distributed catalytic layer and a gradiently distributed material system will cause problems such as excessive use and waste of precious metals and ionomers.
[0004] Based on this, how to develop a fuel cell membrane electrode with hierarchical functional distribution of cathode and anode catalyst layers is an urgent problem to be solved by researchers in this field. Summary of the invention
[0005] In order to solve the technical problems existing in the prior art, the purpose of the present invention is to provide a catalyst slurry and a preparation method and application thereof, as well as a membrane electrode and a fuel cell.
[0006] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:
[0007] A catalyst slurry is prepared by subjecting an ionomer dispersion liquid, a solvent, a catalyst, deionized water and a functional auxiliary agent to a multiple dispersion process.
[0008] A method for preparing a catalyst slurry comprises the following steps:
[0009] S1: mixing the ionomer dispersion with the solvent and then performing tip ultrasound to obtain a first dispersion;
[0010] S2: mixing the first dispersion with a catalyst, deionized water, a solvent, and a functional additive, and then subjecting the mixture to high-speed shearing to obtain a second dispersion;
[0011] S3: The second dispersion is mixed with the solvent, and then subjected to high-pressure homogenization shearing to obtain the desired catalyst slurry.
[0012] Furthermore, in step S1, the step of mixing the ionomer dispersion with the solvent and then performing tip ultrasound to obtain the first dispersion comprises:
[0013] A certain amount of ionomer dispersion is weighed and placed in a closed stirring tank, a certain amount of solvent is weighed and added to the ionomer dispersion, the mass ratio of the ionomer dispersion to the solvent is (0.1-10):1, and under the condition of a circulating cooling water temperature of 5-10°C, a cutting-edge ultrasonic device is used for cutting-edge ultrasonication, the frequency is 12-24kHz, and the output power is 50%-90%, and then the composite material is treated for 10-30 minutes and mixed evenly to obtain a first dispersion.
[0014] Furthermore, in step S2, the first dispersion is mixed with a catalyst, deionized water, a solvent, and a functional additive, and then subjected to high-speed shearing to obtain a second dispersion, comprising:
[0015] The first dispersion, catalyst, deionized water, solvent and functional additive are placed in a closed stirring kettle, wherein the mass ratio of the first dispersion, catalyst, deionized water, solvent and functional additive is (10-20):1:(3-10):(10-25):(10-30). Under the condition of circulating cooling water temperature of 5-10°C, a high-speed shearing process is used to stir the composite materials at 18-30m / s for 30-60min and mix them evenly to obtain a second dispersion.
[0016] Furthermore, in step S3, the second dispersion liquid is mixed with the solvent, and then subjected to high-pressure homogenization shearing to obtain the desired catalyst slurry comprises:
[0017] The second dispersion is placed in the hopper of a high-pressure homogenizing dispersion device, and a solvent is added, wherein the mass ratio of the second dispersion to the solvent is (1-10):1, and the internal circulation shear dispersion is performed for 5-20 times under a shear pressure of 400-1300 bar to obtain the desired catalyst slurry, wherein the solid content of the slurry is 1-5 wt%.
[0018] The invention also discloses an application of the catalyst slurry in preparing the catalyst layer.
[0019] The present invention also discloses a catalyst layer, wherein the catalyst layer is a cathode catalyst layer or an anode catalyst layer, wherein the cathode catalyst layer comprises a cathode first catalyst layer CCL1 and a cathode second catalyst layer CCL2, wherein the anode catalyst layer comprises an anode first catalyst layer ACL1 and an anode second catalyst layer ACL2, wherein the cathode first catalyst layer CCL1 is prepared by spraying a catalyst slurry as described above onto one side of a proton exchange membrane, wherein the functional auxiliary agent in the catalyst slurry of the cathode first catalyst layer CCL1 is one or a combination of cerium oxide, carbon-supported cerium oxide, and iron-doped titanium dioxide, wherein the cathode second catalyst layer CCL2 is prepared by spraying a catalyst slurry as described above onto the surface of the cathode first catalyst layer CCL1, wherein the functional auxiliary agent in the catalyst slurry of the cathode second catalyst layer CCL2 is carbon nanospheres, carbon nanotubes, carbon nanofibers, or the like. The catalyst metal loading in the cathode first catalytic layer CCL1 is not less than the catalyst metal loading in the cathode second catalytic layer CCL2, the ionomer EW value in the cathode first catalytic layer CCL1 is not less than the ionomer EW value in the cathode second catalytic layer CCL2, the anode first catalytic layer ACL1 is made by spraying a catalyst slurry as described above onto the other side of the proton exchange membrane, the functional additive in the catalyst slurry of the anode first catalytic layer ACL1 is one or a combination of polytetrafluoroethylene, graphite sheet, and graphite carbon, the anode second catalytic layer ACL2 is made by spraying a catalyst slurry as described above onto the surface of the anode first catalytic layer ACL1, and the functional additive in the catalyst slurry of the anode second catalytic layer ACL2 is one or a combination of polytetrafluoroethylene, graphite sheet, and graphite carbon.
[0020] The present invention also discloses a membrane electrode, comprising a proton exchange membrane, wherein a cathode first catalytic layer CCL1 is arranged on one side of the proton exchange membrane, and an anode first catalytic layer ACL1 is arranged on the other side opposite to the proton exchange membrane, a cathode second catalytic layer CCL2 is arranged on the side of the cathode first catalytic layer CCL1 away from the proton exchange membrane, and an anode second catalytic layer ACL2 is arranged on the side of the anode first catalytic layer ACL1 away from the proton exchange membrane.
[0021] The present invention also discloses a method for preparing a membrane electrode, comprising the following steps:
[0022] S1: Weigh an appropriate amount of ionomer dispersion, place it in a closed stirring tank, weigh an appropriate amount of solvent, add it to the ionomer dispersion, and use a cutting-edge ultrasonic device to perform cutting-edge ultrasonic treatment at a circulating cooling water temperature of 5-10°C, with a frequency of 12-24kHz and an output power of 50%-90%. Treat the compounded materials for 10-30 minutes and mix them evenly to obtain a first dispersion;
[0023] S2: The first dispersion, catalyst, deionized water, solvent and functional additive are placed in a closed stirring tank, and the composite materials are stirred for 30-60 minutes using a high shear process condition of 18-30 m / s under a circulating cooling water temperature of 5-10°C to obtain a second dispersion;
[0024] S3: placing the second dispersion in a hopper of a high-pressure homogenizing dispersion device, adding an appropriate amount of solvent, and performing internal circulation shear dispersion for 5-20 times at a shear pressure of 400-1300 bar to obtain a catalyst slurry;
[0025] S4: Use ultrasonic spraying equipment to spray the catalyst slurry as the cathode first catalytic layer slurry onto one side of the proton exchange membrane to form the cathode first catalytic layer CCL1, with a nozzle height of 20-30 mm, a nozzle moving linear speed of 150-200 mm / s, a spraying pressure of 1-3 bar, a spraying amount of 1-3 mL / min, and vacuum adsorption drying for 2-10 min;
[0026] S5: repeating steps S1-S4, using ultrasonic spraying equipment to spray the catalyst slurry as the cathode second catalytic layer slurry onto the surface of the cathode first catalytic layer CCL1 to form the cathode second catalytic layer CCL2;
[0027] S6: Repeat steps S1-S4, use ultrasonic spraying equipment to spray the catalyst slurry as the first anode catalytic layer slurry to the other side of the proton exchange membrane to form the first anode catalytic layer ACL1, the nozzle height is 20-30 mm, the nozzle moving linear speed is 150-200 mm / s, the nozzle pressure is 1-3 bar, the spraying amount is 1-3 mL / min, and vacuum adsorption drying is 2-10 min;
[0028] S7: repeating steps S1-S4, using ultrasonic spraying equipment to spray the catalyst slurry as the anode second catalytic layer slurry onto the surface of the anode first catalytic layer ACL1 to form the anode second catalytic layer ACL2.
[0029] The invention also discloses a fuel cell, comprising the membrane electrode as described above.
[0030] Furthermore, in step S1, the ionomer dispersion is one or a combination of Nafion, Aquivion, Flemion, and Aciplex, and the solvent is one or a combination of deionized water, ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol.
[0031] Furthermore, in step S2, the catalyst is one or a combination of Pt / C, PtCo / C, PtNi / C, Ir / C, IrRu / C, and PtRu / C, the catalyst carrier is one or a combination of low specific surface area porous carbon, medium specific surface area porous carbon, high specific surface area porous carbon, and graphite carbon, and the solvent is one or a combination of ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol.
[0032] Furthermore, in step S3, the solvent is one or a combination of ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1) The present invention sequentially obtains a uniform and stable catalyst slurry through cutting-edge ultrasound, high shear dispersion (i.e., high-speed shear dispersion), and high-pressure homogenization shearing process, and then prepares a cathode first catalyst layer slurry, a cathode second catalyst layer slurry, an anode first catalyst layer slurry, and an anode second catalyst layer slurry by adding different functional additives, and finally uses a spraying process to spray to form a catalyst layer, a membrane electrode, and a fuel cell with hierarchical functional distribution of anodes and cathodes;
[0035] 2) The catalyst carrier in the first cathode catalytic layer CCL1 adopts a high specific surface porous carbon carrier, and an appropriate amount of cerium oxide is added to ensure that the product achieves high electrochemical performance while capturing free radicals, further inhibiting the attenuation of the chemical stability of the proton exchange membrane in direct contact with the first cathode catalytic layer CCL1; at the same time, the supported precious metal catalyst particles obtained by the high specific surface porous carbon carrier are fully and evenly wrapped and mixed with the pre-dispersed ionomer polymer, and the ionomer resin molecular chains are fully entangled and cross-linked, so that a liquid-solid phase dispersion uniformly dispersed in the bulk phase can be obtained, and the obtained product is not easy to produce cracks, pinholes, bubbles and other appearance defects;
[0036] 3) The catalyst carrier in the cathode second catalyst layer CCL2 adopts a porous carbon carrier with a medium specific surface area, and adds an appropriate amount of carbon nanotubes with a length of 100-800nm. Due to the cross-linking and steric hindrance effect of the inorganic carbon nanotubes with a high aspect ratio and the organic ionomer, the catalyst layer forms a three-dimensional spatial structure, constructs an effective three-phase interface, reduces the internal mass transfer resistance, and enhances the conductivity and drainage capacity of the catalyst layer;
[0037] 4) The catalyst carrier in the first catalyst layer ACL1 of the anode adopts a graphitized carbon carrier, the catalyst adopts a Pt / C catalyst, and polytetrafluoroethylene hydrophobic material is added to achieve the effective drainage and gas conduction function of the catalyst layer, improve the medium and high electric density mass transfer performance and reverse polarity tolerance characteristics;
[0038] 5) The catalyst carrier of the second anode catalyst ACL2 adopts a graphitized carbon carrier, and the catalyst adopts a supported Ir-based precious metal alloy catalyst to achieve the effective drainage and gas conduction function of the catalyst layer and improve the anti-reverse polarity performance of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic diagram of the structure of the membrane electrode of the present invention;
[0040] Figure 2 The 25 cm membrane electrode assembly prepared in Example 1 of the present invention and Comparative Example 1 2 VI performance curve and electric power density comparison of single battery;
[0041] Figure 3 The 25 cm membrane electrode assembly prepared in Example 1 of the present invention and Comparative Example 1 2 Initial and aging VI performance diagrams of a single cell during catalyst performance testing. DETAILED DESCRIPTION
[0042] The present invention is described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0043] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.
[0044] like Figure 1-3 As shown, a catalyst slurry is prepared by performing a multi-dispersion process on an ionomer dispersion, a solvent, a catalyst, deionized water and a functional auxiliary agent.
[0045] A method for preparing a catalyst slurry comprises the following steps:
[0046] S1: Weigh a certain amount of ionomer dispersion, place it in a closed stirring tank, weigh a certain amount of solvent and add it to the ionomer dispersion, the mass ratio of ionomer dispersion to solvent is (0.1-10):1, use cutting-edge ultrasonic equipment to perform cutting-edge ultrasound under the condition of circulating cooling water temperature of 5-10°C, the frequency is 12-24kHz, the output power is 50%-90%, and then the composite material is treated for 10-30min, mixed evenly, to obtain a first dispersion; using cutting-edge ultrasound, a first dispersion with a fully opened ionomer main chain can be obtained in the solvent system, and after the ionomer main chain is fully opened, defects such as poor product performance consistency caused by ionomer agglomerates in the anode and cathode catalyst layers can be effectively avoided;
[0047] S2: placing the first dispersion, catalyst, deionized water, solvent and functional additive in a closed stirring kettle, wherein the mass ratio of the first dispersion, catalyst, deionized water, solvent and functional additive is (10-20):1:(3-10):(10-25):(10-30), and stirring the composite materials at 18-30 m / s for 30-60 min under the condition of circulating cooling water temperature of 5-10°C by high-speed mechanical shearing process to obtain a second dispersion, wherein the catalyst particles and ionomer resin molecules are fully mixed, uniformly wrapped and stably dispersed, and the ionomer molecules are effectively cross-linked, thereby optimizing the distribution of the three-phase mass transfer interface of the catalyst layer, exposing more catalytic active sites, improving the utilization rate of the catalyst, reducing the resistance to oxygen transmission, and realizing the improvement of the electrochemical performance and power density of the product at high potential;
[0048] S3: Place the second dispersion in the hopper of a high-pressure homogenizing and dispersing device, add a solvent, and use a high-pressure homogenizing and shearing process to perform internal circulation shearing and dispersion for 5-20 times under a pressure of 400-1300 bar to obtain the desired catalyst slurry. The system is uniform and stable, wherein the solid content of the slurry is 1-5wt%, and the mass ratio of the second dispersion to the solvent is (1-10):1.
[0049] The invention discloses the application of the catalyst slurry in preparing a catalyst layer.
[0050] A catalyst layer is a cathode catalyst layer or an anode catalyst layer, wherein the cathode catalyst layer comprises a cathode first catalyst layer CCL1 and a cathode second catalyst layer CCL2, and the anode catalyst layer comprises an anode first catalyst layer ACL1 and an anode second catalyst layer ACL2, wherein the cathode first catalyst layer CCL1 is prepared by spraying a catalyst slurry as described above onto one side of a proton exchange membrane, wherein the functional auxiliary agent in the catalyst slurry of the cathode first catalyst layer CCL1 is one or a combination of cerium oxide, carbon-supported cerium oxide, and iron-doped titanium dioxide, and wherein the cathode second catalyst layer CCL2 is prepared by spraying a catalyst slurry as described above onto the surface of the cathode first catalyst layer CCL1, wherein the functional auxiliary agent in the catalyst slurry of the cathode second catalyst layer CCL2 is one or a combination of carbon nanospheres, carbon nanotubes, and carbon nanofibers. The catalyst metal loading in the cathode first catalytic layer CCL1 is not less than the catalyst metal loading in the cathode second catalytic layer CCL2, the ionomer EW value in the cathode first catalytic layer CCL1 is not less than the ionomer EW value in the cathode second catalytic layer CCL2, the anode first catalytic layer ACL1 is made by spraying a catalyst slurry as described above onto the other side of the proton exchange membrane, the functional auxiliary agent in the catalyst slurry of the anode first catalytic layer ACL1 is one or a combination of several of polytetrafluoroethylene, graphite flakes, and graphite carbon, the anode second catalytic layer ACL2 is made by spraying a catalyst slurry as described above onto the surface of the anode first catalytic layer ACL1, and the functional auxiliary agent in the catalyst slurry of the anode second catalytic layer ACL2 is one or a combination of several of polytetrafluoroethylene, graphite flakes, and graphite carbon.
[0051] A membrane electrode comprises a proton exchange membrane 1, wherein a cathode first catalytic layer CCL12 is arranged on one side of the proton exchange membrane 1, a cathode second catalytic layer CCL23 is arranged on the side of the cathode first catalytic layer CCL12 away from the proton exchange membrane 1, an anode first catalytic layer ACL14 is arranged on the other side opposite to the proton exchange membrane 1, an anode second catalytic layer ACL25 is arranged on the side of the anode first catalytic layer ACL14 away from the proton exchange membrane 1, a cathode gas diffusion layer 6 is arranged on the side of the cathode second catalytic layer CCL23 away from the cathode first catalytic layer CCL12, and an anode gas diffusion layer 7 is arranged on the side of the anode second catalytic layer ACL25 away from the anode first catalytic layer ACL14.
[0052] A method for preparing a membrane electrode comprises the following steps:
[0053] S1: Weigh a certain amount of ionomer dispersion, place it in a closed stirring tank, weigh a certain amount of solvent and add it to the ionomer dispersion, the mass ratio of ionomer dispersion to solvent is (0.1-10):1, use a cutting-edge ultrasonic device to perform cutting-edge ultrasonication under the condition of circulating cooling water temperature of 5-10°C, the frequency is 12-24kHz, the output power is 50%-90%, and then the composite material is treated for 10-30min and mixed evenly to obtain a first dispersion;
[0054] S2: placing the first dispersion, catalyst, deionized water, solvent and functional additive in a closed stirring tank, wherein the mass ratio of the first dispersion, catalyst, deionized water, solvent and functional additive is (10-20):1:(3-10):(10-25):(10-30), stirring the composite materials for 30-60 minutes at a high shear process condition of 18-30 m / s under a circulating cooling water temperature of 5-10°C until they are evenly mixed to obtain a second dispersion;
[0055] S3: placing the second dispersion in a hopper of a high-pressure homogenizing dispersion device, adding a solvent, and performing internal circulation shear dispersion for 5-20 times under a shear pressure of 400-1300 bar to obtain a desired catalyst slurry, wherein the solid content of the slurry is 1-5wt%, and the mass ratio of the second dispersion to the solvent is (1-10):1;
[0056] S4: Use ultrasonic spraying equipment to spray the catalyst slurry as the cathode first catalytic layer slurry onto one side of the proton exchange membrane 1 to form the cathode first catalytic layer CCL1 2, with a nozzle height of 20-30 mm, a nozzle moving linear speed of 150-200 mm / s, a spraying pressure of 1-3 bar, a spraying amount of 1-3 mL / min, and vacuum adsorption drying for 2-10 min;
[0057] S5: repeating steps S1-S4, using ultrasonic spraying equipment to spray the catalyst slurry as the cathode second catalytic layer slurry onto the surface of the cathode first catalytic layer CCL1 2 to form the cathode second catalytic layer CCL2 3;
[0058] S6: Repeat steps S1-S4, use ultrasonic spraying equipment to spray the catalyst slurry as the anode first catalytic layer slurry to the other side opposite to the proton exchange membrane 1 to form the anode first catalytic layer ACL1 4, the nozzle height is 20-30mm, the nozzle moving linear speed is 150-200mm / s, the nozzle pressure is 1-3bar, the spraying amount is 1-3mL / min, and the vacuum adsorption drying is 2-10min;
[0059] S7: repeating steps S1-S4, using ultrasonic spraying equipment to spray the catalyst slurry as the anode second catalytic layer slurry onto the surface of the anode first catalytic layer ACL1 4 to form the anode second catalytic layer ACL2 5;
[0060] S8: A cathode gas diffusion layer 6 is provided on a side of the cathode second catalyst layer CCL2 3 away from the cathode first catalyst layer CCL1 2 , and an anode gas diffusion layer 7 is provided on a side of the anode second catalyst layer ACL2 5 away from the anode first catalyst layer ACL1 4 .
[0061] A fuel cell comprises a membrane electrode as described above.
[0062] In step S1, the ionomer dispersion is one or a combination of commercial Nafion, Aquivion, Flemion, and Aciplex, and the solvent is one or a combination of deionized water, ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol.
[0063] In step S2, the catalyst is one or a combination of Pt / C, PtCo / C, PtNi / C, Ir / C, IrRu / C, and PtRu / C, the catalyst carrier is one or a combination of low specific surface area porous carbon, medium specific surface area porous carbon, high specific surface area porous carbon, and graphite carbon, and the solvent is one or a combination of ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol.
[0064] In step S3, the solvent is one or a combination of ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol.
[0065] The catalyst metal loading in the cathode first catalyst layer CCL1 2 is 50-60%, the EW value of the ionomer dispersion is 800-1000 g / mol, and the I / C ratio is (0.8-1.2):1.
[0066] The catalyst metal loading in the cathode second catalyst layer CCL2 3 is 30-50%, the EW value of the ionomer dispersion is 1000-1200 g / mol, and the I / C ratio is (0.5-1):1.
[0067] The catalyst metal loading in the first catalyst layer ACL1 4 of the anode is 20-30%, the EW value of the ionomer dispersion is 800-1000 g / mol, and the I / C ratio is (1-1.5):1.
[0068] The catalyst metal loading in the second catalyst layer ACL25 of the anode is 20-30%, the EW value of the ionomer dispersion is 720-800 g / mol, and the I / C ratio is (1-1.5):1.
[0069] In steps S4 and S5, the total spraying loading of the cathode catalyst slurry is 0.1-0.2 mg / cm 2 .
[0070] In steps S6 and S7, the total spraying loading of the catalyst slurry on the anode side is 0.05-0.08 mg / cm 2 .
[0071] Example 1
[0072] like Figure 1-3 As shown, a catalyst slurry is prepared by performing a multi-dispersion process on an ionomer dispersion, a solvent, a catalyst, deionized water and a functional auxiliary agent.
[0073] A method for preparing a catalyst slurry comprises the following steps:
[0074] S1: Weigh 5 g of an ionomer dispersion with an EW value of 800 g / mol, place it in a closed jacketed stirred tank, weigh 30 g of isopropanol, add it to the ionomer dispersion, and use a cutting-edge ultrasonic device to perform cutting-edge ultrasonic treatment at a circulating cooling water temperature of 5-10°C, with a frequency of 24 kHz and an output power of 80%. Treat the composite material for 20 minutes and mix it evenly to obtain a first dispersion;
[0075] S2: Weigh 2.92g of the catalyst, fully wet and immerse the catalyst with 10g of deionized water, then add it together with 40g of isopropanol into the first dispersion, place it in a closed jacketed stirring kettle, and use a high-speed mechanical shearing process under the condition of circulating cooling water at 0-5°C to stir and mix the compounded materials at 22m / s for 60min to obtain a second dispersion;
[0076] S3: The second dispersion liquid is placed in the hopper of a high-pressure homogenization dispersion device, 44 g of solvent is added, and a high-pressure homogenization shearing process is adopted to perform internal circulation shearing dispersion 10 times at a shearing pressure of 500 bar to obtain a catalyst slurry.
[0077] A membrane electrode comprises a proton exchange membrane 1, wherein a cathode first catalytic layer CCL12 is arranged on one side of the proton exchange membrane 1, a cathode second catalytic layer CCL23 is arranged on the side of the cathode first catalytic layer CCL12 away from the proton exchange membrane 1, an anode first catalytic layer ACL14 is arranged on the other side opposite to the proton exchange membrane 1, an anode second catalytic layer ACL25 is arranged on the side of the anode first catalytic layer ACL14 away from the proton exchange membrane 1, a cathode gas diffusion layer 6 is arranged on the side of the cathode second catalytic layer CCL23 away from the cathode first catalytic layer CCL12, and an anode gas diffusion layer 7 is arranged on the side of the anode second catalytic layer ACL25 away from the anode first catalytic layer ACL14.
[0078] A method for preparing a membrane electrode comprises the following steps:
[0079] S1: Weigh 5 g of an ionomer dispersion with an EW value of 800 g / mol, place it in a closed jacketed stirred tank, weigh 30 g of isopropanol, add it to the ionomer dispersion, and use a cutting-edge ultrasonic device to perform cutting-edge ultrasonic treatment at a circulating cooling water temperature of 5-10°C, with a frequency of 24 kHz and an output power of 80%. Treat the composite material for 20 minutes and mix it evenly to obtain a first dispersion;
[0080] S2: Weigh 2.92g of catalyst, soak the catalyst with 10g of deionized water, then add it to the first dispersion together with 40g of isopropanol, place it in a closed jacket stirring kettle, and stir and mix the compound materials evenly at 22m / s for 60min under the condition of circulating cooling water at 0-5℃ using a high shear process to obtain a second dispersion;
[0081] S3: placing the second dispersion in a hopper of a high-pressure homogenizing dispersion device, adding isopropanol, wherein the mass ratio of the second dispersion to isopropanol is (1-10):1, and performing internal circulation shear dispersion for 10 times under a shear pressure of 500 bar to obtain a catalyst slurry;
[0082] S4: Use ultrasonic spraying equipment to spray the catalyst slurry as the cathode first catalytic layer slurry onto one side of the proton exchange membrane 1 to form the cathode first catalytic layer CCL1 2, the nozzle height is 30 mm, the nozzle moving linear speed is 150 mm / s, the spraying pressure is 1.5 bar, the spraying amount is 1.5 mL / min, and vacuum adsorption drying is performed for 5 min;
[0083] S5: repeating steps S1-S4, using ultrasonic spraying equipment to spray the catalyst slurry as the cathode second catalytic layer slurry onto the surface of the cathode first catalytic layer CCL1 2 to form the cathode second catalytic layer CCL2 3;
[0084] S6: Repeat steps S1-S4, use ultrasonic spraying equipment to spray the catalyst slurry as the anode first catalytic layer slurry to the other side of the proton exchange membrane 1 to form the anode first catalytic layer ACL1 4, the nozzle height is 30 mm, the nozzle moving linear speed is 150 mm / s, the nozzle pressure is 1.5 bar, the spraying amount is 1.5 mL / min, and vacuum adsorption drying is performed for 5 min;
[0085] S7: repeating steps S1-S4, using ultrasonic spraying equipment to spray the catalyst slurry as the anode second catalytic layer slurry onto the surface of the anode first catalytic layer ACL1 4 to form the anode second catalytic layer ACL2 5;
[0086] S8: A cathode gas diffusion layer 6 is provided on a side of the cathode second catalyst layer CCL2 3 away from the cathode first catalyst layer CCL1 2 , and an anode gas diffusion layer 7 is provided on a side of the anode second catalyst layer ACL2 5 away from the anode first catalyst layer ACL1 4 .
[0087] The formula of the catalyst slurry used in the cathode first catalytic layer CCL1 2, the cathode second catalytic layer CCL2 3, the anode first catalytic layer ACL1 4, and the anode second catalytic layer ACL2 5 is shown in Table 1.
[0088] Table 1
[0089]
[0090]
[0091] Example 2
[0092] The difference between this embodiment and embodiment 1 is that the parameters of the catalyst and ionomer used in the preparation method of the catalyst slurry of this embodiment are different. The parameters of the catalyst and ionomer used in the preparation method of the catalyst slurry of embodiment 2 are shown in Table 2.
[0093] Table 2
[0094]
[0095] The rest is the same as in Example 1.
[0096] Example 3
[0097] The difference between this embodiment and embodiment 1 is that the parameters of the catalyst and ionomer used in the preparation method of the catalyst slurry of this embodiment are different. The parameters of the catalyst and ionomer used in the preparation method of the catalyst slurry of embodiment 3 are shown in Table 3.
[0098] Table 3
[0099]
[0100] The rest is the same as in Example 1.
[0101] Example 4
[0102] The difference between this embodiment and embodiment 1 is that the parameters of the catalyst and ionomer used in the preparation method of the catalyst slurry of this embodiment are different. The parameters of the catalyst and ionomer used in the preparation method of the catalyst slurry of embodiment 4 are shown in Table 1.
[0103] The rest is the same as in Example 1.
[0104] Table 4
[0105]
[0106] The spraying amount of the catalyst slurry of Examples 1-4 is shown in Table 5.
[0107] Table 5
[0108]
[0109] Comparative Example 1
[0110] The difference between this comparative example and Example 1 is that the membrane electrode structure of this comparative example is different from that of Example 1 and does not contain the anode second catalyst layer ACL25.
[0111] Comparative Example 2
[0112] The difference between this comparative example and Example 1 is that the membrane electrode structure of this comparative example is different from that of Example 1 and does not contain the anode first catalyst layer ACL14.
[0113] Comparative Example 3
[0114] The difference between this comparative example and Example 1 is that the membrane electrode structure of this comparative example is different from that of Example 1 and does not contain the cathode second catalyst layer CCL2 3.
[0115] Comparative Example 4
[0116] The difference between this comparative example and Example 1 is that the membrane electrode structure of this comparative example is different from that of Example 1 and does not contain the cathode first catalyst layer CCL1 2.
[0117] The membrane electrode structures of Comparative Examples 1-4 are shown in Table 6.
[0118] Table 6
[0119]
[0120] The membrane electrode performance test scheme is as follows:
[0121] (1) High-purity hydrogen (1.5 L / min) was distributed to the anode and air (2 L / min) was distributed to the cathode. The relative humidity of the anode was set to 20%, the humidity of the cathode was set to 50%, the anode inlet pressure was 80 kPa, the cathode inlet pressure was 70 kPa, and the stack temperature was 75°C. The current was loaded to the maximum and activated at a constant current for 30 minutes under hydrogen and oxygen conditions. Then the cathode was switched to air. After the voltage was stable for about 15 minutes, the initial VI performance of the membrane electrode was obtained by testing.
[0122] (2) High-purity hydrogen (0.5 L / min) was distributed to the anode and air (0.5 L / min) was distributed to the cathode. The relative humidity of the anode was set to 45%, the humidity of the cathode was set to 45%, the anode inlet pressure was 50 kPa, the cathode inlet pressure was 50 kPa, the stack temperature was 60 °C, and the initial ECSA of the membrane electrode was obtained by testing.
[0123] (3) High-purity nitrogen (1 L / min) was distributed to the anode and air (1 L / min) was distributed to the cathode. The relative humidity of the anode was set to 90%, and the humidity of the cathode was set to 90%. The anode inlet pressure was normal pressure, the cathode inlet pressure was normal pressure, the stack temperature was 60°C, and the reverse polarity tolerance test was stopped after 40 minutes. After the anode and cathode were purged with dry gas for 30 minutes, the VI performance of the sample was tested, and the reverse polarity tolerance capability was obtained by comparing the initial VI performance of the membrane electrode.
[0124] (4) High-purity hydrogen (0.2 L / min) was distributed to the anode and nitrogen (0.075 L / min) was distributed to the cathode, the relative humidity of the cathode and anode was set to 100%, the cathode and anode inlet pressure was normal pressure, and the stack temperature was 80°C. A square wave cycle of 0.6 V for 3 s and 0.95 V for 3 s was performed to perform a catalyst aging test, where BOL refers to the hydrogen / air VI polarization measurement result before the start of the catalyst aging test, and EOL refers to the hydrogen / air VI polarization measurement result after the end of the catalyst aging test.
[0125] The performance results of the membrane electrodes prepared in Examples 1-4 and Comparative Examples 1-4 are shown in Table 7.
[0126] Table 7
[0127]
[0128]
[0129] Depend on Figure 2 As shown in Table 7, Examples 1-4 all exhibit higher electrochemical initial performance, aging performance and anti-reverse polarity characteristics than Comparative Examples 1-4. In the functionalized membrane electrode prepared by the catalyst slurry of the present invention, the electrochemical performance of Example 1 can achieve 0.755V@0.8A / cm 2 、0.561V@2A / cm 2 , while the membrane electrode with uniformly distributed catalyst layer prepared under conventional conditions, such as Comparative Examples 1-4, has an initial electrochemical performance drop of about 20-40 mV@0.8 A / cm 2 、60-70mV@2A / cm 2 The initial electrochemical active area ECSA of Example 1 can reach 67m 2 / g, which is about 17% higher than that of comparative example 1. In the small and medium current density ranges, the electrochemical performance of the membrane electrode of Example 1 is almost not attenuated after the catalyst aging performance test, while the performance of comparative example 1 is attenuated to varying degrees in the entire current density range, especially in the large current density range, the attenuation amplitude reaches 10-30mV, and the performance of Example 1 decreases by only 6mV@0.8A / cm under the reverse polarity condition for 40min. 2In comparative example 2, when the anode does not have the first anode catalyst layer ACL1 4 and the hydrophobic regulator, the performance decreases to 19mV@0.8A / cm 2 , the reverse polarity performance drops by more than 3 times. When the anode does not have the anode second catalytic layer ACL2 5, such as in Comparative Example 1, the reverse polarity performance drops by about 8 times.
[0130] according to Figure 3 It can be concluded that compared with comparative example 1, embodiment 1 has a higher output power density in the entire power density range, and the peak power density of the former can reach 1.12 W / cm 2 , which is about 16% higher than the latter.
[0131] Parts or structures not specifically described in the present invention may adopt existing technologies or existing products and will not be described in detail here.
[0132] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A catalyst layer, characterized in that: The catalyst layer is a cathode catalyst layer or an anode catalyst layer, the cathode catalyst layer includes a cathode first catalyst layer CCL1 and a cathode second catalyst layer CCL2, the anode catalyst layer includes an anode first catalyst layer ACL1 and an anode second catalyst layer ACL2, the cathode first catalyst layer CCL1 is made by spraying catalyst slurry onto one side of a proton exchange membrane, the functional auxiliary agent in the catalyst slurry of the cathode first catalyst layer CCL1 is one or a combination of cerium oxide, carbon-supported cerium oxide, and iron-doped titanium dioxide, the cathode second catalyst layer CCL2 is made by spraying catalyst slurry onto the surface of the cathode first catalyst layer CCL1, and the functional auxiliary agent in the catalyst slurry of the cathode second catalyst layer CCL2 is one or a combination of carbon nanospheres, carbon nanotubes, and carbon nanofibers The catalyst metal loading in the cathode first catalyst layer CCL1 is not less than the catalyst metal loading in the cathode second catalyst layer CCL2, the ionomer EW value in the cathode first catalyst layer CCL1 is not less than the ionomer EW value in the cathode second catalyst layer CCL2, the anode first catalyst layer ACL1 is made by spraying the catalyst slurry onto the other side of the proton exchange membrane, the functional additive in the catalyst slurry of the anode first catalyst layer ACL1 is one or a combination of polytetrafluoroethylene, graphite sheet, and graphite carbon, the anode second catalyst layer ACL2 is made by spraying the catalyst slurry onto the surface of the anode first catalyst layer ACL1, and the functional additive in the catalyst slurry of the anode second catalyst layer ACL2 is one or a combination of polytetrafluoroethylene, graphite sheet, and graphite carbon; The catalyst slurry is prepared by a multiple dispersion process of an ionomer dispersion, a solvent, a catalyst, deionized water and a functional additive; The method for preparing the catalyst slurry comprises the following steps: S1: mixing the ionomer dispersion with the solvent and then performing tip ultrasound to obtain a first dispersion; S2: mixing the first dispersion with a catalyst, deionized water, a solvent, and a functional additive, and then subjecting the mixture to high-speed shearing to obtain a second dispersion; S3: mixing the second dispersion with the solvent, and then subjecting the mixture to high-pressure homogenization shearing to obtain the desired catalyst slurry; In step S1, the ionomer dispersion is mixed with a solvent and then subjected to tip ultrasound to obtain a first dispersion, comprising: Weigh a certain amount of ionomer dispersion, place it in a closed stirring tank, weigh a certain amount of solvent and add it to the ionomer dispersion, the mass ratio of the ionomer dispersion to the solvent is (0.1-10): 1, use a cutting-edge ultrasonic device to perform cutting-edge ultrasound at a circulating cooling water temperature of 5-10°C, the frequency is 12-24kHz, the output power is 50%-90%, and then the composite material is treated for 10-30 minutes and mixed evenly to obtain a first dispersion; In step S2, the first dispersion is mixed with a catalyst, deionized water, a solvent, and a functional additive, and then subjected to high-speed shearing to obtain a second dispersion, comprising: The first dispersion, catalyst, deionized water, solvent and functional additive are placed in a closed stirring kettle, wherein the mass ratio of the first dispersion, catalyst, deionized water, solvent and functional additive is (10-20):1:(3-10):(10-25):(10-30), and the composite materials are stirred for 30-60 minutes at 18-30 m / s under the condition of circulating cooling water temperature of 5-10°C using a high-speed shear process to mix uniformly to obtain a second dispersion; In step S3, the second dispersion liquid is mixed with the solvent, and then subjected to high-pressure homogenization shearing to obtain the desired catalyst slurry, comprising: The second dispersion is placed in a hopper of a high-pressure homogenizing dispersion device, and a solvent is added, wherein the mass ratio of the second dispersion to the solvent is (1-10): 1, and the internal circulation shear dispersion is performed for 5-20 times under a shear pressure of 400-1300 bar to obtain the desired catalyst slurry, wherein the solid content of the slurry is 1-5wt%; The catalyst carrier in the first cathode catalyst layer CCL1 adopts a high specific surface porous carbon carrier, and an appropriate amount of cerium oxide is added to ensure that the product achieves high electrochemical performance while capturing free radicals, further inhibiting the attenuation of the chemical stability of the proton exchange membrane in direct contact with the first cathode catalyst layer CCL1; at the same time, the supported precious metal catalyst particles obtained by the high specific surface porous carbon carrier are fully and evenly wrapped and mixed with the pre-dispersed ionomer polymer, and the ionomer resin molecular chains are fully entangled and cross-linked to obtain a liquid-solid phase dispersion uniformly dispersed in the bulk phase; The catalyst carrier in the cathode second catalyst layer CCL2 adopts a porous carbon carrier with a medium specific surface area, and adds a proper amount of carbon nanotubes with a length of 100-800nm. Due to the cross-linking and steric hindrance effect of the inorganic carbon nanotubes with a high aspect ratio and the organic ionomer, the catalyst layer forms a three-dimensional spatial structure, constructs an effective three-phase interface, reduces the internal mass transfer resistance, and enhances the conductivity and drainage capacity of the catalyst layer; The catalyst carrier in the first catalyst layer ACL1 of the anode adopts a graphitized carbon carrier, the catalyst adopts a Pt / C catalyst, and polytetrafluoroethylene hydrophobic material is added to realize the effective drainage and gas conduction function of the catalyst layer, improve the medium and high electric density mass transfer performance and reverse polarity tolerance characteristics; The catalyst carrier in the anode second catalyst ACL2 adopts a graphitized carbon carrier, and the catalyst adopts a supported Ir-based precious metal alloy catalyst to achieve the effective drainage and gas conduction function of the catalytic layer and improve the membrane electrode anti-reverse polarity performance.
Citation Information
Patent Citations
Catalyst slurry for fuel cell, preparation method thereof and membrane electrode
CN111952611A
Membrane electrode of gradient proton exchange membrane fuel cell as well as preparation method and application of membrane electrode
CN113991126A
Preparation method of fuel cell membrane electrode catalyst slurry
CN114039059A